2012
DOI: 10.5897/ajfs11.192
|View full text |Cite
|
Sign up to set email alerts
|

Effects of processing methods on nutrient retention and contribution of white yam (Dioscorea rotundata) products to nutritional intake of Nigerians

Abstract: Consumption of indigenous foods is being encouraged globally as a means of meeting dietary needs of people. Yam products constitute staple source of energy to many Nigerians but little is documented on their nutrient composition. This study was carried out to determine the effects of processing methods on nutrient retention and possible contribution of some diets prepared from yam to nutrient intake of consumers. Fresh yam tubers were purchased from Sango market in Ibadan, peeled and cut into small pieces, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
10
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 14 publications
8
10
7
Order By: Relevance
“…On the other hand, Polycarp et al (2012) reported that carbohydrate in different yam varieties range from 77.5 to 87.3 g/100g. However, the carbohydrate content in fried yams in this study were lower than the reported carbohydrate content (53.8 g/100g) obtained in fried yam (Adepoju, 2012) previously. The lower carbohydrate content in this study could be due to pre-boiling of samples prior to frying.…”
Section: Resultscontrasting
confidence: 95%
See 2 more Smart Citations
“…On the other hand, Polycarp et al (2012) reported that carbohydrate in different yam varieties range from 77.5 to 87.3 g/100g. However, the carbohydrate content in fried yams in this study were lower than the reported carbohydrate content (53.8 g/100g) obtained in fried yam (Adepoju, 2012) previously. The lower carbohydrate content in this study could be due to pre-boiling of samples prior to frying.…”
Section: Resultscontrasting
confidence: 95%
“…It is obvious that differences in yam samples and processing methods play significant role in determining nutrient content of various yambased meals commonly consume in Nigeria and other African countries. The low fibre content in fried yam samples (0.9 -2.0 g/100g) concur with previous findings of 1.2 g/100g in fried yam (Adepoju, 2012). Other studies showed fibre content of between 0.39 g/100g and 7.69 % in yams processed in various ways ranging from raw, boiled, pounded, porridge, etc.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The fermented flour were low in moisture and fat content, which is an indication that they can be kept for a period of time before they go bad. They were moderate in protein content compared with that of other plant-based staples used for complementary foods such as yam and rice (Adepoju, 2012;Otegbayo et al, 2001). However, the two fermented flour were high in ash, total carbohydrates and gross energy content.…”
Section: Proximate Compositionmentioning
confidence: 99%
“…The fermented flour were however low in all the water soluble vitamins except vitamin B 12 . The low level of these vitamins is believed to be due to the extent of soaking of the fermented sample, as it has been reported that soaking food samples for a period of time leads to leaching of the water soluble micronutrients into the soaking water (Adepoju et al, 2010, Adepoju, 2012. Addition of M. bellicosus powder led to remarkable increase in the β-carotene content of the enriched foods, the increment being due to the vitamin A content of the insect, which has been previously reported to be a good source of vitamin A (330.42±0.12 µg/100g, Adepoju & Omotayo, 2014).…”
Section: Vitamin Composition Of Fermented Flour and Enriched Complemementioning
confidence: 99%